BART Perks: Using Incentives to Manage Transit Demand. Issue 8 (December 2018) - Greene-Roesel, Ryan; Castiglione, Joe; Guiriba, Camille; Bradley, Mark
BART Perks, offered by Bay Area Rapid Transit (BART) and the San Francisco County Transportation Authority (SFCTA), was a six-month test program that provided incentives to riders for traveling during the shoulder hours of the morning peak period. The main goals of the Perks program were to: (1) reduce peak period and peak direction crowding, and improve person throughput; (2) improve BART customer satisfaction; (3) increase employer support for flexible work schedules; and (4) identify implementation challenges and solutions to provide lessons learned. About 17, 800 participants enrolled, and about 2, 600 of them were frequent weekday peak hour travelers. During the trial, an average of 250 participants, or about 10% of those who previously traveled during the peak hour, shifted their ride to one of the shoulder hours. Recommendations for future programs include recruiting a larger number of riders in the targeted travel market, structuring it to better reward behavior change rather than preexisting behavior, and considering more efficient methods of participant recruitment and retention.